SILVER NANOPARTICLES: ECOFRIENDLY SURFACE STERILIZATION OF PLANT SEEDS IN DIFFERENT SHAPES AND SIZES - P. Nartop (Journal of Animal and Plant Sciences, 2019)
In this study, silver nanoparticles obtained via green synthesis were utilized for the surface sterilization of seeds in different shapes and sizes. Water extracts of dried Alkanna tinctoria rhizomes and Pinus nigra leaves were utilized in the bioreduction of silver ions. Centaurea cyanus L., Digitalis purpurea L., Calendula officinalis L., Lavandula officinalis L. and Melissa officinalis L.seeds were exposed to silver nanoparticle colloidal solutions (Alkanna-NP and Pinus-NP) for 1-20 mins for surface sterilization. Germination and sterilization percentages of the seeds were recorded during four weeks. Pinus-NP was found more effective on surface sterilization (85.11%) than Alkanna-NP (74.77%). The germination percentages of the different genus seeds were recorded according to the applied silver nanoparticle sterilization (Alkanna- NP and Pinus-NP), respectively: C. cyanus 40.56% and 57.78%; D. purpurea 89.44% and 52.22%; C. officinalis 18.87% and 13.89%; L. officinalis 15.56% and 17.22%. No germination was observed at M. officinalis seeds. There was no negative effect was detected during culture period on both seeds and sterile plantlets. Silver nanoparticles were also found more effective on rough-coated seed surface sterilization with regard to NaOCl. It was proved that both Alkanna-NP and Pinus-NP can be used as sterilization agents in plant tissue cultures.
Keywords: surface sterilization; plant seed; silver nanoparticle; Alkanna tinctoria; Pinus nigra